Innovative Water Management at the Environmental Campus Birkenfeld - Helling, Klaus; Bölsche, Dorit Schumann (Journal of Sustainability Perspectives, 2021)
Sustainable water management has a high relevance for universities and this paper describes the innovative water management system at the Environmental Campus Birkenfeld (ECB), which belongs to Trier University of Applied Sciences. The ECB is called the "greenest university" in Germany. Not without reason, because in the GreenMetric Ranking 2018 and 2019 the ECB took sixth place worldwide and was No. 1 in Germany. Ever since the foundation of the ECB, sustainable development and circular economy have been the main focus of all activities of the university. In the sustainability strategy, a holistic approach following the German Sustainability Code is pursued, which includes teaching, research, knowledge transfer and university operation. In 2019 the Environmental Campus achieved in the GreenMetric category water, the full score of 1000 points. As part of an integrated zero emissions concept ECB ́s water management system is based on a meticulously planned water conservation program which includes technological- and management-based solutions to achieve sustainable water resource use at ECB. Within the ECB ́s wastewater reduction and resource recovery initiative a research project on “Zero Emission Water Management and Nutrient Mining” is converting an existing dormitory in such a way that the separate collection and discharge of the partial streams grey and black water is possible.